Correction: Liu et al. (2024). “Walking with Dreams”: The Categories of Career Decision-Making Self-Efficacy and Its Influence on Learning Engagement of Senior High School Students. Behavioral Sciences, 14(12), 1174 - Xuejun Liu; Xiongjie Mei; Guojun Ji (Behavioral Sciences)
The authors would like to adjust the author order for the following two reasons: 1 [...]